Synthesis and Optical Property of ZnO/SiO2 Nanocomposite Cryogels - Su, Lifen; Miao, Lei; Zhang, Ming; Qian, Jiasheng; Xia, Ru; Yang, Bin; Chen, Peng (Asian Journal of Chemistry, 2014)
In this paper, ZnO cryogels with a dopant of SiO2 with molar ratio of 9:1 to 1:1 were prepared by sol-gel technology and dried by a novel vacuum freeze drying using a co-precursor method. The as-prepared ZnO/SiO2 nanocomposites were annealed in air at 250, 500 and 800 ºC for 45 min, respectively. The structure and morphology of the nanocomposites were determined by X-ray diffraction (XRD) and field emission scanning electron microscopy. The optical properties were estimated not only by UV-visible spectrometer but also theoretical calculation. The annealed nanocomposites exhibited hexagonal Wurtzite structure ZnO and whose crystallinity became better as an increase of annealing temperature. The amounts of doping SiO2 affect the optical band gaps and morphology of ZnO/SiO2 nanocomposites significantly. After annealing, the obtained ZnO nanorods grow up in size from the SEM images with annealing temperature ranging from 250 to 500 ºC and flowerlike ZnO was formed with tetragonal pillars at 800 ºC.